PREVALENCE OF TURNER’S SYNDROME - Faiz, Nadhira; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Gonadal dysgenesis, 45 X condition, also known as Turner’s syndrome, is the condition in which a female is missing X monosomy partially or completely. There might be a difference in the signs and symptoms seen in the affected. There are many areas of concern which are to be checked regularly like cardiovascular malformations, hearing impairment and low thyroid function. There has been no discovery of a treatment to cure this gonadal dysgenesis. However, each of the symptoms can be reduced to help the patient live a more productive life and can reach his or her almost fullest potentials in the work they do or commitment they take up further in life.